Кирило Розумовський: Спроба встановлення спадкового гетьманства - Сухих, Л.; Вовк, О. (Архіви України, 2008)
The publication deals with four petitions to the Russian Empress Catherine II submitted by Lubens’kyi, Hadiats’kyi, Kyivs’kyi and Myrhorods’kyi regiments with regard to implementation of the Rozumovs’kys hereditary hetmanate in Ukraine. Signed by major sergeants and the gentry, the petitions were written in February, 1764. The article also includes historical retrospective: it describes numerous attempts (starting from Bogdan Khmelnyts’kyi) with respect to establishment of hereditary hetmanate which would have been of significant importance for strengthening and development of Ukrainian Kozak state.